The impact of rest duration on work intensity and RPE during interval training - Seiler, S.; Hetlelid, K. J. (Medicine & Science in Sports & Exercise, 2005)
Purpose: To investigate the effect of rest duration on self-selected intensity, physiological responses, and RPE during a standardized, high-intensity interval training prescription.